The only official prep guide from the makers of the ACT (New Jersey, 2017)
he book contains information on how to register for the exam, proven test-taking strategies, ideas for preparing mentally and physically, gearing up for test day, and much more. This invaluable guide includes additional questions and material that contains articles on everything from preparing a standout college application and getting into your top-choice school to succeeding in college
Keywords: Đánh giá ACT,ACT Assessment,College entrance achievement tests,Thi tuyển sinh đại học; United States,Hoa Kỳ